2003
DOI: 10.1038/sj.bjc.6601241
|View full text |Cite
|
Sign up to set email alerts
|

Membranous location of EGFR immunostaining is associated with good prognosis in renal cell carcinoma

Abstract: Epidermal growth factor receptor (EGFR) is a key factor in tumorigenesis. The association between EGFR expression and prognosis in renal cell carcinoma (RCC) is not clear. In our study of 134 RCCs, the cellular location of immunostaining was evaluated and patients with EGFR-positive tumours with prominent membranous staining had a good prognosis. Their overall survival was significantly longer (P ¼ 0.004) than that of patients with either EGFR-negative tumours or with mainly cytoplasmic staining. However, furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
1
18
2
1
Order By: Relevance
“…The study population consisted of 138 consecutive patients who underwent radical nephrectomy for renal cell carcinoma (RCC) between 1994 and 1999, and who were followed according to a protocol including regular visits and examinations at Tampere University Hospital, as shown in a previous study (25). Median age of the patients at time of operation was 64 years (range 35–86 years).…”
Section: Methodsmentioning
confidence: 99%
“…The study population consisted of 138 consecutive patients who underwent radical nephrectomy for renal cell carcinoma (RCC) between 1994 and 1999, and who were followed according to a protocol including regular visits and examinations at Tampere University Hospital, as shown in a previous study (25). Median age of the patients at time of operation was 64 years (range 35–86 years).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of an EGFRvIII alteration in patients with RCC has not been reported previously to the best of our knowledge. A study by Kallio et al (2003) reported that the overall survival was significantly higher in patients with RCC who had noticeable immunostaining for membranous EGFR (Kallio et al, 2003). However, this finding was challenged by Modjtahedi and Cunningham (2005), who stated that the antibody used for EGFR immunostaining in the Kallio et al paper was a polyclonal rabbit anti-EGFR variant III antibody (Modjtahedi and Cunningham, 2005).…”
Section: Molecular Signatures Of Oeff Specimens Tested By Ocav1mentioning
confidence: 99%
“…EGFR inspite of being a promising target in cancer therapy, yet failed to acquire definitive, sensitive potential accurate molecular predictors of sensitivity to EGFR inhibitors for patients having gastro-esophageal cancers [36]. The dichotomous cytoplasmic and membranous staining in other tumors holds prognostic significance as reported in renal cell carcinoma [37] with its association with worsening progression and prognosis [38]. In gastric cancer, however, such confirmation yet remains to be done.…”
Section: Discussionmentioning
confidence: 99%